Youth Participatory Action Research. INKLA Project ? Preventing Bullying in Secondary School. Photovoice ? Advantages and Disadvantages of School, Class and a Peer Group - Wójcik, Małgorzata; Mondry, Maria (INSTED: Interdisciplinary Studies in Education & Society, 2017)
This article presents two youth participatory action research (YPAR) projects initiated by secondary school students and supported by university researchers and students. The main goal of the project INKLA was to help secondary school students explore intragroup relations in school classes and problems the students encounter, such as peer group exclusion, conflicts and bullying. A group of secondary school and university students became researchers and conducted interviews in their school classes which resulted in planning a research-based collective action to prevent bullying and improve the school life. Photovoice shows different aspects of peer relationships from the point of view of secondary school and university students The outcomes demonstrate that the student voice can support school?s anti-bullying programs if the responsibility for bullying prevention is shared with students. It also shows that participatory action research can influence and shift the decision making process in school.